Diet-dependent function of the extracellular matrix proteoglycan Lumican in obesity and glucose homeostasis - Wolff, Gretchen; Weinmann, Jonas; Billeter, Adrian; Müller, Beat P.; Herzig, Stephan; Grimm, Dirk (Molecular metabolism, 2019)
Objective - Extracellular matrix remodeling is required for adipose expansion under increased caloric intake. In turn, inhibited expandability due to aberrant collagen deposition promotes insulin resistance and progression towards the metabolic syndrome. An emerging role for the small leucine-rich proteoglycan Lumican in metabolically driven nonalcoholic fatty liver disease sparks an interest in further understanding its role in diet-induced obesity and metabolic complications. - Methods - Whole body ablation of Lumican (Lum−/−) gene and adeno-associated virus-mediated over-expression were used in combination with control or high fat diet to assess energy balance, glucose homeostasis as well as adipose tissue health and remodeling. - Results - Lumican was found to be particularly enriched in the stromal cells isolated from murine gonadal white adipose tissue. Likewise murine and human visceral fat showed a robust increase in Lumican as compared to fat from the subcutaneous depot. Lumican null female mice exhibited moderately increased fat mass, decreased insulin sensitivity and increased liver triglycerides in a diet-dependent manner. These changes coincided with inflammation in adipose tissue and no overt effects in adipose expandability, i.e. adipocyte formation and hypertrophy. Lumican over-expression in visceral fat and liver resulted in improved insulin sensitivity and glucose clearance. - Conclusions - These data indicate that Lumican may represent a functional link between the extracellular matrix, glucose homeostasis, and features of the metabolic syndrome.